c-Rel is required for the development of thymic Foxp3(+) CD4 regulatory T cells - Isomura, Iwao (The Rockefeller University Press, 2009)
During thymopoiesis, a unique program of gene expression promotes the development of CD4 regulatory T (T reg) cells. Although Foxp3 maintains a pattern of gene expression necessary for T reg cell function, other transcription factors are emerging as important determinants of T reg cell development. We show that the NF-κB transcription factor c-Rel is highly expressed in thymic T reg cells and that in c-rel(−/−) mice, thymic T reg cell numbers are markedly reduced as a result of a T cell–intrinsic defect that is manifest during thymocyte development. Although c-Rel is not essential for TGF-β conversion of peripheral CD4(+)CD25(−) T cells into CD4(+)Foxp3(+) cells, it is required for optimal homeostatic expansion of peripheral T reg cells. Despite a lower number of peripheral T reg cells in c-rel(−/−) mice, the residual peripheral c-rel(−/−) T reg cells express normal levels of Foxp3, display a pattern of cell surface markers and gene expression similar to those of wild-type T reg cells, and effectively suppress effector T cell function in culture and in vivo. Collectively, our results indicate that c-Rel is important for both the thymic development and peripheral homeostatic proliferation of T reg cells.